Efektivitas Penggunaan aplikasi Identitas Kependudukan Digital (IKD) sebagai penunjang Pelayanan Administrasi Kependudukan di Kota Tanjungpinang (International Forum of Researchers and Lecturers, 2025)
The use of the Digital Population Identity (IKD) application in Tanjungpinang City aims to provide convenience and protection to the public in accessing digital population administration services. However, distrust of the digital system is also a barrier. The public often feels worried about the security of their personal data and the reliability of the system used. In addition, counseling and training for the public on the use of information technology is often lacking, resulting in low community involvement in existing services. The purpose of this study was to measure the effectiveness of the use of the Digital Population Identity (IKD) application in terms of population administration in Tanjungpinang City. The method used is a descriptive quantitative method with a population of 1,271 people and a sample of 93 people, and using data collection tools in the form of documentation and filling out questionnaires or surveys using Subagyo's theory (2000) on indicators of effectiveness measurement. The results of the study showed that the accuracy of the target with an average value of 77.00, the implementation of program socialization 75.38, the achievement of program objectives 75.90, and the implementation of program monitoring 77.70. Based on the results above, it is concluded that the categorization of the quality and performance of the IKD Application user unit obtained a survey conversion result of 75.53 IKD Application Users at quality C which is included in the